Reducing regional flow stasis and improving intraventricular hemodynamics with a tipless inflow cannula design: An in vitro flow visualization study using the EVAHEART LVAD. Issue 9 (9th June 2019) - May‐Newman, Karen; Montes, Ricardo; Campos, Josue; Marquez‐Maya, Nikolas; Vu, Vi; Zebrowski, Erin; Motomura, Tadashi; Benkowski, Robert
Abstract: Due to the high stroke rate of left ventricular assist device (LVAD) patients, reduction of thrombus has emerged as an important target for LVAD support. Left ventricular blood flow patterns with areas of flow stasis and recirculation are associated with platelet aggregation, which is worsened by exposure to high shear stress. Previous reports of intraventricular thrombus in LVAD patients have identified the outside of the LVAD inflow cannula as a nidus for LV thrombus formation. Previous studies of LVAD inflow cannula design have shown a region of low blood velocity and pulsatility at the apex, adjacent to the cannula. One unresolved question is whether the standard practice of inserting the LVAD inflow cannula several mm into the LV could be revised to reduce thrombus formation. To address this, a "tipless" inflow cannula was designed for the EVAHEART LVAS, and assessed in a mock circulatory loop of the LVAD‐supported heart. Customized transparent silicone models of a dilated LV were connected to the EVAHEART LVAS at the apex with a clear polycarbonate inflow cannula for flow visualization using particle image velocimetry (PIV). The "tipless" cannula was inserted flush with the endocardial border and did not protrude into the LV. This condition was compared to the standard cannula position with a 1‐cm insertion into the LV. The Pre‐LVAD condition corresponded to a severe heart failure patient (ejection fraction of 24%) with a dilated LV (180 mL). LVAD support was provided at speeds of 1.8 and 2.3 krpm. At the lower LVAD speed, 63% of the flow passed through the LVAD, with the remainder ejecting through the aortic valve. When LVAD speed was increased, nearly all flow (98%) left the LV through the LVAD. Both LVAD speed conditions produced a vortex ring similar to the Pre‐LVAD condition in diastole. However, the protruding inflow cannula interrupted the growth and restricted the movement of the vortex, and produced areas of low velocity and pulsatility adjacent to the cannula. The tipless cannula exhibited an uninterrupted pattern of the mitral jet toward the LV apex, which allowed the diastolic vortex to grow and aid in the washout of this region. In addition, the tipless cannula increased aortic valve flow, which reduces stasis in the left ventricular outflow tract. The EVAHEART LVAS tipless inflow cannula design improved regional velocity, pulsatility, and vortex formation compared to the standard protruding design, which all reduce the risk of thrombus formation. The clinical significance of the differences observed in the flow field will be dependent on other factors such as the cannula material and surface characteristics, as well as the patients' coagulation status.